2013
DOI: 10.1007/s11010-013-1692-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNAs involved in dexamethasone-induced muscle atrophy

Abstract: MicroRNAs (miRNAs), a novel class of post-transcriptional gene regulators, have been demonstrated to be involved in several cellular processes regulating the expression of protein-coding genes. To investigate the mechanisms of miRNA-mediated regulation during the process of muscle atrophy, we performed miRNA microarray hybridization between normal differentiated C2C12 cells and dexamethasone (DEX)-treated C2C12 cells. We observed that 11 miRNAs were significantly up-regulated and six miRNAs were down-regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…Recent evidence suggests that miRNAs are involved in modulation of atrophy, proliferation and differentiation of skeletal muscles (20,24,25). A previous study observed that miR-351 is transiently increased in early days of muscle regeneration (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that miRNAs are involved in modulation of atrophy, proliferation and differentiation of skeletal muscles (20,24,25). A previous study observed that miR-351 is transiently increased in early days of muscle regeneration (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of miRNAs in muscle-associated biological processes has not been fully investigated. To our knowledge, it has only been reported that miR-1 and miR-133 are able to promote differentiation and proliferation of the skeletal and cardiac muscle cells (19), and the expression of miR-351 in differentiated C2C12 cells is upregulated following treatment with dexamethasone (20). The underlying mechanisms, however, are still to be further explored.…”
Section: Introductionmentioning
confidence: 92%
“…This suggests that the endogenous levels of miR-181 are normally sufficient to reach effect-exerting plateau [116]. Other regulators of the balance between proliferation and differentiation in myogenic cells are miR-322 and miR-503, which target cell cycle promoter Cdc-25a, although the evidence is at present limited to one myoblast cell line in vitro [117,118]. As in cardiac myogenesis, epigenetic and post-transcriptional controls are complexly entwined with miRs in skeletal muscle formation [119].…”
Section: Skeletal Myogenesis and Mirsmentioning
confidence: 99%
“…Growing evidence has suggested that miRNAs participate in a series of biological processes such as cell proliferation, apoptosis, immune response, as well as many diseases 12,13) .…”
Section: Introductionmentioning
confidence: 99%